Microinjection of monoclonal antibody to protein p53 inhibits serum-induced DNA synthesis in 3T3 cells. - Mercer, W E (1982)
Monoclonal antibody directed against the transformation-related protein p53 was microinjected manually into the nuclei of quiescent Swiss 3T3 mouse cells. The cells were subsequently stimulated with 10% fetal calf serum. Microinjection of p53 antibody at or around the time of serum stimulation clearly inhibited the subsequent entry of Swiss 3T3 cells into the S phase of the cell cycle. p53 antibody had no effect on serum-stimulated DNA synthesis when it was microinjected 4 hr or later after serum stimulation. Monoclonal antibody to an unrelated antigen, Lyt-2.2, had no effect on serum-stimulated DNA synthesis regardless of the time it was microinjected. Under similar experimental conditions, p53 antibody had no effect on simian virus 40- or adenovirus 2-induced DNA synthesis. These experiments add strength to the suggestion that p53 is involved in the regulation of cell proliferation.